A heterologous AZD1222 priming and BNT162b2 boosting regimen more efficiently elicits neutralizing antibodies, but not memory T cells, than the homologous BNT162b2 regimen. Issue 10 (3rd March 2023) - Baek, Yae Jee; Kim, Woo-Joong; Ko, Jae-Hoon; Lee, Youn-Jung; Ahn, Jin Young; Kim, Jung Ho; Jang, Ho Cheol; Jeong, Hye Won; Kim, Yong Chan; Park, Yoon Soo; Kim, Sung-Han; Peck, Kyong Ran; et al.
Abstract: Background: Comparative analyses of SARS-CoV-2-specific immune responses elicited by diverse prime-boost regimens are required to establish efficient regimens for the control of COVID-19. Method: In this prospective observational cohort study, spike-specific immunoglobulin G (IgG) and neutralizing antibodies (nAbs) alongside spike-specific T -cell responses in age-matched groups of homologous BNT162b2/BNT162b2 or AZD1222/AZD1222 vaccination, heterologous AZD1222/BNT162b2 vaccination, and prior wild-type SARS-CoV-2 infection/vaccination were evaluated. Results: Peak immune responses were achieved after the second vaccine dose in the naïve vaccinated groups and after the first dose in the prior infection/vaccination group. Peak titers of anti-spike IgG and nAb were significantly higher in the AZD1222/BNT162b2 vaccination and prior infection/vaccination groups than in the BNT162b2/BNT162b2 or AZD1222/AZD1222 groups. However, the frequency of interferon-γ-producing CD4 + T cells was highest in the BNT162b2/BNT162b2 vaccination group. Similar results were observed in the analysis of polyfunctional T cells. When nAb and CD4 + T -cell responses against the Delta variant were analyzed, the prior infection/vaccination group exhibited higher responses than the groups of other homologous or heterologous vaccination regimens. Conclusion: nAbs are efficiently elicited by heterologous AZD1222/BNT162b2 vaccination, as well as prior infection/vaccination, whereas spike-specific CD4 + T -cell responses are efficiently elicited by homologous BNT162b2 vaccination. Variant-recognizing immunity is more efficiently generated by prior infection/vaccination than the other homologous or heterologous vaccination regimens.